Electronic Medical Record Management in Monitoring Loan and Return of Medical Records at Majalaya Hospital - Haryati, Sri; Syahidin, Yuda; Widyaningrum, Desy (International Journal Software Engineering and Computer Science (IJSECS), 2023)
This study aims to develop an electronic-based governance system for monitoring borrowing and returning medical record files at Majalaya Hospital. The Waterfall method was chosen as the main approach because the detailed and structured nature of this method allows planned and scheduled development. This approach also guarantees the quality of the resulting system, as each phase is completed in stages, avoiding over-reliance on a single stage. System development documentation is well organized, where each phase must be completed comprehensively before the next step can be carried out. One of the problems identified related to borrowing medical record files is the absence of an expedition book to record borrowing and returning. The existence of this expedition book is critical in monitoring the distribution of medical record files. Therefore, the authors designed a management system in accordance with the procedures for borrowing and returning medical record files. This system is expected to be able to efficiently monitor the distribution of medical records and organize borrowing and return processes more smoothly. With the existence of an effective monitoring mechanism, it is hoped that it can reduce potential problems that may occur when borrowing and returning medical records, even being able to deal with them proactively